Transformational Leadership Development Patterns In Realizing Effective Madrasah (Multisite Study At Madrasah Aliyah Negeri Deli Serdang Regency) - Ahmad Mukhlasin; Candra Wijaya; Siti Halimah (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The purpose of this research is to discuss the pattern of developing transformational leadership in creating effective madrasah (Multisite Study at Madrasah Aliyah Negeri Deli Serdang Regency). This research uses a multi-site qualitative research method, which was conducted at MAN 1 Deli Serdang and MAN 2 Deli Serdang. The results of this study concluded that the Head of MAN Deli Serdang carried out leadership with a Transformational model in accordance with the theory of M Bass and BJ. Valio which consists of 4 aspects viz.ideal influence, inspirational motivation, intellectual stimulus, as well as individual considerations that are maximally applied so as to increase the effectiveness of madrasas at MAN Deli Serdan. The Pattern of Transformational Leadership Development for the Head of MAN Deli Serdang in Creating Effective Madrasas by applying Transformational Leadership According to Bass and Valio, namely ideal influence, inspirational motivation, intellectual stimulus, and individual considerations by also implementing development, namely digital Leadership, Tangible, Reliability, Responsiveness, with this development will increase transformational leadership in realizing effective madrasas.